Prevalence of Hypothyroidism in Infertile Women and Evaluation of Response of Treatment for Hypothyroidism on Infertile - Awan , Amber Farid; Naqvi , Sadiqa Batool; Nayyar , Shazia; Ghani , Naureen; Sajjad , Rabia; Nawaz , Qudsia (Indus Journal of Bioscience Research, 2025)
Background: Thyroid disease, especially hypothyroidism, is frequently associated with infertility, which affects 8–10% of couples globally. Ovulation, pregnancy outcomes, and menstrual function are all impacted by thyroid problems. Early thyroid examination and therapy are necessary because infertility has been linked to both overt and subclinical hypothyroidism. Objective: The main objective of this study was to ascertain the incidence of hypothyroidism in infertile women and how it affects the results of reproduction. To evaluate the relationship between thyroid dysfunction and infertility, autoimmune markers and thyroid hormone levels were analyzed. Methodology: 130 infertile women who visited fertility clinics participated in a qualitative study. To evaluate thyroid status, participants performed thyroid function tests (TSH, T3, T4, and thyroid antibodies). Menstrual patterns, length of infertility, and medical histories were documented. To assess changes in ovulatory function and reproductive outcomes, responses to levothyroxine medication were tracked throughout time. Results: According to the study, hypothyroidism was present in 63.1% of infertile women, with subclinical hypothyroidism accounting for 40% and overt hypothyroidism for 23.1%. Treatment with levothyroxine improved pregnancy chances by restoring ovulation in 60% of overt hypothyroid cases and 73.1% of subclinical instances. Conclusion: Infertility outcomes are greatly impacted by hypothyroidism, which is very common in infertile women. Levothyroxine treatment enhances ovulation and conception, underscoring the importance of early thyroid screening in the treatment of infertility.